2001
DOI: 10.1100/tsw.2001.311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Soil Removal on Dynamics of Dissolved Inorganic Nitrogen in a Snow-Dominated Forest

Abstract: To clarify the effect of vegetation and surface soil removal on dissolved inorganic nitrogen (N) dynamics in a snow-dominated forest soil in northern Japan, the seasonal fluctuation of N concentrations in soil solution and the annual flux of N in soil were investigated at a treated site (in which surface soil, including understory vegetation and organic and A horizons, was removed) and control sites from July 1998 to June 2000. Nitrate (NO3) concentration in soil solution at the treated site was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Recently, it has been reported that the removal of S. kurilensis from a birch (Betula ermanii Cham) forest significantly increased the growth of the birch trees (Takahashi et al, 2003) due to greater availability of soil water. Ozawa et al (2001) have shown the effect of surface soil and vegetation removal on the dynamics of dissolved inorganic N in soil solution. Thus, an investigation on the growth and substrate quality of fine root in relation to altered soil N availability due to understory vegetation removal will be of great help in understanding the tree-undergrowth interaction for soil nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the removal of S. kurilensis from a birch (Betula ermanii Cham) forest significantly increased the growth of the birch trees (Takahashi et al, 2003) due to greater availability of soil water. Ozawa et al (2001) have shown the effect of surface soil and vegetation removal on the dynamics of dissolved inorganic N in soil solution. Thus, an investigation on the growth and substrate quality of fine root in relation to altered soil N availability due to understory vegetation removal will be of great help in understanding the tree-undergrowth interaction for soil nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nitrate leaching induced by forest management has been reported in a north Japanese forest with removal of surface soil and understory vegetation by scarification (Ozawa et al 2001;Shibata et al 2007), which is a treatment to promote regeneration of forests with avoidance of dominance of a single understory plant (Sasa senanensis). Nitrification and nitrate concentrations in soil water increased in the site with scarification, and were leached out in early spring by snow melt.…”
Section: Forest Managementmentioning
confidence: 98%
“…Intensive soil disturbances such as soil scarification, as well as cultivation (Song et al 2005), can expose the ground to direct sunlight and increase soil temperature. The resultant high decomposition rate may limit the accumulation of organic matter during the age-sequences (Ozawa et al 2001). …”
Section: Discussionmentioning
confidence: 99%